Immuno-Engineering of Hematopoietic Stem Cells for Durable Immune Resistance to HIV: From the CCR5Δ32 Mutation to Autologous Gene Therapies Mediated by Lentiviral Vectors - Barack Ndenga (Publisher, 2025)
Rare cases of sustained HIV remission following hematopoietic stem cell transplantation demonstrate that durable,systemic resistance to HIV is a biological possibility. These exceptional outcomes have fundamentally reframed the cure agenda, establishing a new paradigm: the host immune system can be engineered for intrinsic resistance. This review examines the immuno-engineering of hematopoietic stem cells (HSCs) as a foundational strategy to reconstitute a permanently HIV-resistant immune system. We trace the conceptual evolution from the protective CCR5Δ32 mutation to modern autologous therapies using lentiviral vectors and genome-editing technologies. We critically analyze the biological rationale, technological platforms, clinical progress, and translational challenges of HSC-based resistance, positioning engineered immunity not as a futuristic concept, but as the cornerstone of a durable, one-time curative intervention. Keywords : HIV cure,Hematopoietic stem cells (HSCs),Gene therapy,Immuno-engineering,CCR5,Lentiviral vectors,Genome editing (CRISPR-Cas9),Autologous transplantation,Immune reconstitution,Viral entry inhibition,Berlin patient,HIV resistance,CD4+ T cells,Translational medicine,Durable remission
Rare cases of sustained HIV remission following hematopoietic stem cell transplantation have demonstrated that durable,systemic resistance to HIV is a biological possibility. These exceptional outcomes have fundamentally reframed the cure agenda, establishing a new paradigm: the host immune system can be engineered for intrinsic resistance. This review examines the immuno-engineering of hematopoietic stem cells (HSCs) as a foundational strategy to reconstitute a permanently HIV-resistant immune system. I trace the conceptual evolution from the protective CCR5Δ32 mutation to modern autologous therapies using lentiviral vectors and genome-editing technologies. I critically analyze the biological rationale, technological platforms, clinical progress, and translational challenges of HSC-based resistance, positioning engineered immunity as the cornerstone of a durable, one-time curative intervention.